The color of crime : racial hoaxes, white crime, media messages, police violence, and other race-based harms - Russell-Brown, Katheryn, 1961- (New York University Press, 2021)
"A powerful, engaging book that critiques the history of race, law, and justice by examining where race lives and breathes across the U.S. criminal-legal system"--